Role of Da'wah in Responding to Political Dynamics in Indonesia - Hasibuan, Hamdi Maulana; Sazali, Hasan; Sayekti, Retno (Journal of Modern Islamic Studies and Civilization, 2025)
This study explores the role of da'wah in responding to the dynamic political landscape in Indonesia. As a form of religious communication deeply rooted in cultural values, da'wah has the potential to shape political behavior, raise awareness, and foster inclusive participation, particularly among marginalized groups such as women. The findings indicate that da'wah serves not only as a medium for conveying moral and ethical principles but also as an instrument for political education and engagement. By utilizing both traditional and digital media, da'wah adapts to contemporary challenges and facilitates dialogue across political divides. However, the study also identifies several challenges, including the risks of misinformation, misinterpretation, and the politicization of religious messages. These issues highlight the need for da'wah practitioners to develop effective communication strategies that are contextually relevant and grounded in both religious knowledge and socio-political understanding. Innovative approaches such as philanthropic da'wah, participatory platforms, and interdisciplinary engagement are emphasized as key to enhancing the impact of da'wah in political discourse. Using a qualitative literature review method this study provides a comprehensive analysis of how da'wah can contribute to building political awareness and democratic values in Indonesia. The study concludes that with the right strategies and ethical foundations, da'wah can become a powerful tool for civic transformation and social cohesion.